Determinants Of Murabahah Finance At Islamic Commercial Banks In Indonesia - Fahmi Ali Kurniawan; Ashari Lintang Yudhanti (LPPM ISNJ Bengkalis, 2023)
This research aims to analyze the influence of return on assets (ROA), non-performing financing (NPF), and financing-to-deposit ratio (FDR) on murabahah financing at Islamic Commercial Banks (ICB). This quantitative research uses secondary data from the annual Islamic Banking Statistics (IBS) report published by the Financial Services Authority (FSA) for 2015-2021. The population and sample in this study consisted of all ICBs in Indonesia registered with the FSA, namely 15. The sampling technique used saturated samples. Meanwhile, the data used is the overall financial condition of ICB in the research year consisting of 12 months x 7 periods = 84 data. The data analysis technique uses the partial least square-structural equation model (PLS-SEM). The research results show that ROA does not influence murabahah financing, while NPF and FDR influence murabahah financing negatively and significantly. The implications of this research complement the existing theory, and practically, it can be a reference for Islamic banks in increasing ROA, reducing NPF, and increasing FDR through third-party funds so that murabahah financing can increase and more people are helped.